The Cambridge handbook of lifespan development of creativity - Russ, Sandra W. ca. 20./21. Jh; Hoffmann, Jessica D. ca. 20./21. Jh; Kaufman, James C. 1974- (Cambridge University Press, 2022)
This handbook focuses on the development and nurturance of creativity across the lifespan, from early childhood to adolescence, adulthood, and later life. It answers the question: how can we help individuals turn their creative potential into achievement? Each chapter examines various contexts in which creativity exists, including school, workplace, community spaces, and family life. It covers various modalities for fostering creativity such as play, storytelling, explicit training procedures, shifting of attitudes about creative capacity, and many others. The authors review research findings across disciplines, encompassing the work of psychologists, educators, neuroscientists, and creators themselves, to describe the best practices for fostering creativity at each stage of development